Atrial flutter ablation through the azygous continuation in a patient with mirror image dextrocardia and interrupted inferior vena cava - Greyling, Adèle; Potts, James (SA Heart Journal, 2019)
Arrhythmias are frequent in adult congenital heart disease (ACHD). Most common is cavotricuspid isthmus (CTI)-dependent atrial flutter (AFL), followed by scar (incisions / patches)-related circuits. Radiofrequency catheter ablation (RFCA) is the treatment of choice. Linear radiofrequency (RF) applications are required, usually via a femoral approach. We describe a case of CTI-dependent AFL ablation by the femoral approach in a patient with dextrocardia and interrupted inferior vena cava (IVC).